Pengaruh Return on Asset, Cash Ratio, Total Asset Turnover, dan Debt to Equity Ratio Terhadap Nilai Perusahaan: Studi pada Perusahaan Sektor Basis Material Industri Wadah dan Kemasan - Jeanneth Stefany Patty; Astrid Dita Meirina Hakim (CV. Ulil Albab Corp, 2024)
This study aims to investigate the partial effects of return on assets, cash ratio, total asset turnover, and debt to equity ratio on company value in the Basic Materials sector of the packaging industry listed on the Indonesia Stock Exchange from 2019 to 2023. The sample of this study consists of 14 companies in the Basic Materials sector of the packaging industry listed on the Indonesia Stock Exchange from 2019 to 2023. The research employs panel data regression statistical analysis tools assisted by Eviews version 12 software and Microsoft Excel 2013. The results indicate that debt to equity ratio has a partial positive and significant effect on company value. On the other hand, return on assets, cash ratio, and total asset turnover have no partial significant effect on company value.